The poem electric : technology and the American lyric - Perlow, Seth (University of Minnesota Press, 2018)
"An enlightening examination of the relationship between poetry and the information technologies increasingly used to read and write it. Many poets and their readers believe poetry helps us escape straightforward, logical ways of thinking. But what happens when poems confront the extraordinarily rational information technologies that are everywhere in the academy, not to mention everyday life? Examining a broad array of electronics--including the radio, telephone, tape recorder, Cold War-era computers, and modern-day web browsers--Seth Perlow considers how these technologies transform poems that we don't normally consider "digital." From fetishistic attachments to digital images of Emily Dickinson's manuscripts to Jackson Mac Low's appropriation of a huge book of random numbers originally used to design thermonuclear weapons, these investigations take Perlow through a revealingly eclectic array of work, offering both exciting new voices and reevaluations of poets we thought we knew. With close readings of Gertrude Stein, Frank O'Hara, Amiri Baraka, and many others, The Poem Electric constructs a distinctive lineage of experimental writers, from the 1860s to today. Ultimately, Perlow mounts an important investigation into how electronic media allows us to distinguish poetic thought from rationalism. Posing a necessary challenge to the privilege of information in the digital humanities, The Poem Electric develops new ways of reading poetry, alongside and against the electronic equipment that is now ubiquitous in our world"--